Efecto en los parámetros productivos e indicadores organolépticos de la inclusión del contenido ruminal deshidratado en el balanceado de pollos - Capelo Davila, Marlin Stefany (2018)
The industry that is dedicated to the farms of different species, try to use new raw materials as an alternative for the feeding of the animals, so that complicates the use and handling of raw materials for the small and medium producers, however, can these decrease in imports of raw materials with the use of products that are in our area. The present research work was carried out on the premises of the farm "Santa Inés", belonging to the Academic Unit of Sciences Agriculture of the Technical University of Machala of El Oro province, was used 160 chickens cobb 500, the same that were randomly distributed in five experimental groups with five different diets (treatments) and in four repetitions for each treatment. The treatments were, on the basis of the addition of the flour of ruminal contents dehydrated (percent), the following: T1 (0%), T2 (3 %), T3 (4 %), T4 (5%) and T5 (6%) of ruminal contents dehydrated in the balanced food. The studied variables were: consumption of food and water, weight gain, feed conversion, live weight, weight of the carcase, mortality rates and indicators organoleptic as odor, flavor, tenderness and juiciness of meat subjected to a test of cupping with the participation of a panel of 70 people selected at random. For what was given numeric value for three qualitative categories: excellent, good and bad with the exception of the tenderness that were 2 categories soft or hard. In order to obtain the weights of the channel is had to fish 1 chicken of each treatment and each replica, random either this female or male and with the data obtained was used the experimental design analysis of a factor (ANOVA), by what program was used for the Statgraphics is analyzed data as: live weight (g), water consumption, food consumption, index of conversion and production parameters of the channel that were the following: weight bloody, weight without feathers, weight without head, neck and legs, weight with liver and gizzard and finally the weight without viscera. For the rest of the variables are not used any statistical program is only represented its value in percentages for the data from: Weight of breast frozen, weight of breast thawed weight without skin, weight of the breast cooked, weight of the juice as well as for the indicators organoleptic is led them to simple comparison in percentages as the taste, odour, flavor, tenderness, juiciness. The results show that the addition of flour of ruminal contents in the diet, influences parameters as productive as live weight, weight gain, feed consumption and conversion rate, reaching the best results to 6 % of inclusion, without influence on the consumption of water and with some negative impact on the rate of mortality, crescendo from 4 to 6%, a result which should be examined in greater detail in his explanation. Presents No influence in relation to the weight of the carcase, nor in the indicators organoleptic except in the indicator flavor, rejected in the survey of tasting by consumers in the level 6%. As you increase your level of inclusion, decreases the cost per pound of balanced.